2009
DOI: 10.1080/10428190903064824
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of mature B-cell non Hodgkin lymphoma involving bone marrow and peripheral blood: critical analysis and insights gained at a tertiary care cancer hospital

Abstract: We evaluated the diagnostic utility of flow cytometry immunophenotyping in bone marrow aspirates and peripheral blood, in the assessment of mature B-cell non-Hodgkin lymphoma (MBNHL). We analyzed 356 cases of MBNHL received for immunophenotyping over a 4 year period. All cases were reviewed, correlated with biopsy specimen (lymph node and splenectomy). Discrepant cases were re-evaluated. Common subtypes included chronic lymphocytic leukemia (CLL) (243 cases, 68.5%), follicular lymphoma (30 cases, 8.5%), mantle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
3
11
2
Order By: Relevance
“…Gujral et al 19 showed that 13 (43%) of 30 patients with FL in the peripheral blood and bone marrow had CD23+ disease, whereas Garcia et al 16 and Xu et al 17 reported rates of 73% and 78% CD23+ FL in their series of 62 and 24 lymph node cases, respectively. The frequency of CD23 expression at diagnosis of FL detected in our study is similar to the results from the latter 2 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gujral et al 19 showed that 13 (43%) of 30 patients with FL in the peripheral blood and bone marrow had CD23+ disease, whereas Garcia et al 16 and Xu et al 17 reported rates of 73% and 78% CD23+ FL in their series of 62 and 24 lymph node cases, respectively. The frequency of CD23 expression at diagnosis of FL detected in our study is similar to the results from the latter 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…13 The flow cytometric evaluation of FL has received particular attention in studies specifically focusing on FL or as part of immunophenotypic evaluation of non-Hodgkin B-cell lymphomas. [14][15][16][17][18][19] The conclusions drawn from these studies were useful in providing a refined immunophenotypic profile and, thus, improved accuracy of FL diagnosis. While CD23 was assessed in flow cytometry panels used by various investigators, no specific association was reported with morphologic or clinical characteristics.…”
mentioning
confidence: 99%
“…These results, along with CD23 negativity and the absence of a history of lymphocytosis excluded a chronic lymphoid leukemia diagnosis. 7,8 Considered together, these findings indicated that this case was de novo CD5 + DLBCL. Although hemophagocytosis was seen on the BM smear and laboratory findings indicated the progression of thrombocytopenia with coagulopathy, the two disease entities could not be definitely distinguished.…”
Section: Discussionmentioning
confidence: 97%
“…25,26 Between 70%-78% of nodal FLs are reported to be CD23 positive; 25,26 however, lower percentages are reported in peripheral blood and bone marrow samples (43%). 27 Olteanu et al showed that CD23 expression in FLs was associated with a better overall and event free survival, and CD23(-) FLs were more commonly seen in grade 3 cases. 28 In our study, 1 of 2 grade 3 cases were CD23(+); due to low numbers of grade 3 cases, we were not able to meaningfully evaluate CD23 expression between the low and high histologic grade cases.…”
Section: Discussionmentioning
confidence: 99%